Predicting Postsecondary Education and Employment Outcomes Using Results From the Transition Assessment and Goal Generator. (May 2018) - Burnes, Jennifer J.; Martin, James E.; Terry, Robert; McConnell, Amber E.; Hennessey, Maeghan N.
We conducted an exploratory study to investigate the relation between nonacademic behavior constructs measured by the Transition Assessment and Goal Generator (TAGG) and postsecondary education and employment outcomes for 297 high school leavers who completed the TAGG during their high school years. Four of eight TAGG constructs predicted postsecondary educational outcomes: (a) Interacting With Others, (b) Student Involvement in the Individualized Education Program (IEP), (c) Support Community, and (d) Goal Setting and Attainment. Four constructs predicted postsecondary employment outcomes: (a) Employment, (b) Student Involvement in the IEP, (c) Support Community, and (d) Interacting With Others. The addition of student grade point average (GPA) strengthened some of the models. The findings appear to add predictive validity evidence to support use of TAGG results to assist with transition planning.